Real‐world tyrosine kinase inhibitor treatment pathways, monitoring patterns and responses in patients with chronic myeloid leukaemia in the United Kingdom: the UK TARGET CML study. (24th May 2020) - Milojkovic, Dragana; Cross, Nicholas C. P.; Ali, Sahra; Byrne, Jenny; Campbell, Gavin; Dignan, Fiona L.; Drummond, Mark; Huntly, Brian; Marshall, Scott; McMullin, Mary Frances; Neelakantan, Pratap; Raghavan, Manoj; et al.
Summary: Management of chronic myeloid leukaemia (CML) has recently undergone dramatic changes, prompting the European LeukemiaNet (ELN) to issue recommendations in 2013; however, it remains unclear whether real‐world CML management is consistent with these goals. We report results of UK TARGET CML, a retrospective observational study of 257 patients with chronic‐phase CML who had been prescribed a first‐line TKI between 2013 and 2017, most of whom received first‐line imatinib ( n  = 203). Although 44% of patients required ≥1 change of TKI, these real‐world data revealed that molecular assessments were frequently missed, 23% of patients with ELN‐defined treatment failure did not switch TKI, and kinase domain mutation analysis was performed in only 49% of patients who switched TKI for resistance. Major molecular response (MMR; BCR‐ABL1 IS ≤0·1%) and deep molecular response (DMR; BCR‐ABL1 IS ≤0·01%) were observed in 50% and 29%, respectively, of patients treated with first‐line imatinib, and 63% and 54%, respectively, receiving a second‐generation TKI first line. MMR and DMR were also observed in 77% and 44% of evaluable patients with ≥13 months follow‐up, receiving a second‐generation TKI second line. We found little evidence that cardiovascular risk factors were considered during TKI management. These findings highlight key areas for improvement in providing optimal care to patients with CML.